Determinan Loyalitas Nasabah pada Perbankan Syariah: Analisis Peran Switching behavior - Lailatul Maslakhah; Muhammad Nizar; Abdillah Mundir (Kartika: Jurnal Studi Keislaman, 2026)
This study analyzes the influence of service quality, sharia compliance, and digital banking on customer loyalty, with switching behavior as a mediating variable among customers of Bank Syariah Indonesia (BSI) KCP Pandaan. Using an explanatory quantitative approach, primary data were collected from 100 respondents through purposive sampling and analyzed using SmartPLS-based SEM. The results show that sharia compliance has a negative and significant effect on switching behavior, meaning stronger implementation of sharia principles reduces customers' tendency to switch banks. However, service quality and digital banking show no significant effect on switching behavior. Switching behavior is also found unable to mediate the relationships between the independent variables and customer loyalty. These findings confirm that loyalty in Islamic banking is driven more by commitment to sharia principles than by functional service or digital technology. The study is limited to one branch office with a small sample, so further testing across broader areas is needed. Practically, Islamic banks should strengthen sharia compliance as their main strategy to retain customers. This research offers a fresh perspective on switching behavior by positioning sharia compliance as the primary determinant of customer loyalty amid increasingly intense banking competition